Application of SFRA for diagnostics on medical isolation transformers. (May 2020) - Bucci, G.; Ciancetta, F.; Fioravanti, A.; Fiorucci, E.; Prudenzi, A.
Highlights: A low-cost SFRA device to checking transformers in hospital environments is proposed. Faults of IT-M transformers have effects on health care facilities and diagnostic rooms. Some IT-M defects are frequent and well known, others are rarer and less obvious. SFRA on IT-M transformers improves the resilience of critical electrical systems. The adoption of SFRA is useful both from an economic and safety point of view. Abstract: Medical environments must guarantee the electrical safety of medical personnel and, especially, of patients in contact with electro-medical devices. These environments are equipped with IT-M distribution systems, where an isolation transformer transfers the electricity while the devices are isolated from the power source. This safety system works reliably only if the isolation transformer is functioning properly. A failure of this transformer also involves high risks when the supplied equipment is in direct contact with the patient. A system for the online diagnosis of these transformers could play a crucial role in terms of safety, allowing their state to be analyzed and their reliability assessed over time. The SFRA technique represents a possible solution to monitor the status and prevent breakdowns. SFRA is a non-invasive technique that allows the evaluation of the integrity of the transformer without applying high voltages. In critical installation it could be automatically carried out on a daily basis, through a low-cost measuring device, connected in parallel to the transformer. In this paper we proposed a low-cost SFRA test system. We also investigated the most common types of faults affecting IT-M transformers and carried out experimental tests on a set of single-phase isolation transformers for medical use, in order to correlate the TF diagrams with the most common deteriorations and defects.